THE EFFECTIVENESS OF NASAL CALCITONIN AND CALCITRIOL COMBINATION THERAPY IN POSTMENOPAUSAL OSTEOPOROSIS - Saime Sarıoğlu Ay; Haydar Gök; Peyman Yalçın (Archives of Rheumatology, 2005)
This study was prepared to investigate the efficacy of calcitonin nasal spray and calcitriol combination therapy in the treatment of postmenopausal osteoporosis. 520 women between 45-70 years of age were enrolled for assessment. Among them, 200 patients who were suitable according to medical history, physical examination, laboratory parameters and bone mineral density (BMD) measurements were recruited and randomized into 4 seperate treatment groups. The first group was treated with 200 IU/day nasal calcitonin and calcitriol 0.25 µgx2, the second group with 200 IU/day nasal calcitonin, the third group with calcitriol 0.25 µgx2, and fourth group with 1000 mg/day calcium alone. The first three groups were also given 1000 mg/day calcium. Patents were assessed at baseline and 6 months intervals. Overall follow-up duration was 2 years. Markers of bone formation and resorption were measured at 6 months intervals. Measurement of BMD values were done at the onset and at the end of first and second year. The increase in the measurements of lumbar spine and femoral neck BMD was higher in the combination group. We concluded that combination therapy in the form of nasal calcitonin, calcitriol and calcium was more effective in increasing BMD values as opposed to the nasal calcitonin or calcitriol therapy alone in the treatment of postmenopausal osteoporosis.